The Effect of Topical Gel Ethanol Extract of Gotu Kola Leaf (Centella Asiatica (L.) Urban) on Wound Healing in a White Male Rat (Rattus Norvegicus) Induced by Streptozotocin - I Dewa Ayu Sudiari Dewi; Nurmawati Fatimah; Sutji Kuswarini (Surabaya Physical Medicine and Rehabilitation Journal, 2023)
Background: Diabetes mellitus (DM) can have a number of consequences, one of which is diabetic neuropathy, which can cause sores, notably in patients' feet. Wound therapy with synthetic drugs in diabetes is still not functioning as well as expected. Centella Asiatica (L.) Urban has been demonstrated to promote wound healing through a variety of mechanisms, including collagen synthesis stimulation, fibroblast proliferation stimulation, antiulcer, antibacterial, and antioxidant activity. Pharmaceutical treatments for wound healing are routinely utilized upon the assumption that a moist wound is a gel. Aims: The purpose of this study was to see how a topical gel ethanol extract of gotu kola (Centella Asiatica (L.) Urban) promoted wound healing in streptozotocin (STZ)-induced white male rats (Rattus Norvegicus). Methods: This is an experimental study using twenty white male rats (Rattus Norvegicus) caused by STZ. The rats were placed into four groups, each with five rats. These four groups are the control group, the treatment group P1 (ethanol gel gotu kola leaf at 2.5% concentration), the treatment group P2 (ethanol gel gotu kola leaf at 5% concentration), and the treatment group P3 (ethanol gel gotu kola leaf at 10% concentration). STZ was used to promote blood sugar elevation in the rats. The wound healing rate was estimated by comparing the wound healing rates of each group using macroscopic observation. Result: The findings of this study revealed that extract gel gotu kola leaf concentration applied to the wound on days 4, 7, 11, and 14 has a statistically significant influence on wound healing (p=0.000). Conclusion: Based on the research conducted, it can be concluded that gotu kola extract gel has a significant influence on the rats' wound healing.